A novel method of variable flow operation in district cooling system: A case study. (March 2023) - Zhang, Wei; Jin, Xu; Zhang, Ling; Hong, Wenpeng
Abstract: The district cooling system (DCS) is generally considered to be a key efficient cooling technology to cope with the increasing cooling demand. However, the energy consumption of pumps in DCS accounts for a large proportion. This work demonstrated a novel variable flow control strategy based on measured operating parameters. An existing DCS in a subtropical climate zone was used as the baseline model, denoted as Case A . Furthermore, using TRNSYS software, the variable flow control of the chilled water pumps and the cooling water pumps in Case A was performed in turn, and two variable flow models were established, denoted as Case B and Case C, respectively. The operation strategies capable of dealing with the diversified cooling loads were developed and simulated. The results indicated that compared with Case A, the newly proposed models Case B and Case C reduced the energy consumption by 9.50% and 14.15%, cut down CO2 emissions by 9.45% and 14.18%, saved costs by 10.34% and 15.16%, respectively. Moreover, the efficiency of the two models was also improved by 10.70% and 16.67%, respectively, compared with the Case A . Effective operation strategies can further improve the performance of DCS, thereby providing energy-saving and efficient cooling solutions. Graphical abstract: Image 1